1-MCP maintains postharvest quality in winter jujube during low-temperature storage by regulating energy and sugar metabolism and enhancing antioxidant capacity - Tang, Wen; Xiang, Biao; Cao, Yang; Wu, Cuiyun; Zhang, Chuanjiang; Lin, Minjuan; Du, Peihua (Frontiers in Plant Science, 2025)
This study investigates the effects of 1-methylcyclopropene (1-MCP) treatment on postharvest storage of winter jujube. The results indicate that after 1-MCP treatment, the pyruvate (PA) content in winter jujube decreased by 20% at 30 days compared to the control. The energy charge (EC), ATP, and ADP levels increased by 7%, 17%, and 27%, respectively. Activities of key enzymes involved in energy metabolism, including succinate dehydrogenase (SDH), cytochrome c oxidase (COX), H+-ATPase, and Ca2+-ATPase were elevated. Furthermore, the activities of acid invertase (AI) and neutral invertase (NI) were 27% and 26% lower, respectively, than those in the control. Sucrose synthase (SS) activity increased by 52%, while the activities of hexokinase (HK) and phosphofructokinase (PFK) decreased by 19% each. Activities of key antioxidant enzymes-superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and glutathione reductase (GR)-were significantly enhanced. Non-enzymatic antioxidants, including vitamin C (VC), flavonoids, total phenols, and reduced glutathione (GSH) contents, were effectively retained, and suppressing the accumulation of the hydrogen peroxide (H2O2) and malondialdehyde (MDA). These findings suggest that 1-MCP treatment preserves the postharvest quality of winter jujube by enhancing energy metabolism, delaying sugar metabolism, and improving antioxidant capacity.